2010
DOI: 10.1080/00981381003648398
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Sensitive Interventions and Health and Behavioral Health Youth Outcomes: A Meta-Analytic Review

Abstract: Despite Census Bureau projections that youth from minority cultures will comprise the majority of the nation's youth in approximately a decade, little research has been conducted on culturally sensitive interventions (CSIs). Accordingly, this study sought to determine: (1) the effectiveness of CSIs designed to address health and behavioral health outcomes, (2) whether effectiveness varies depending on the class or type of outcome, and (3) whether race/ethnicity moderates effectiveness. The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…To assess this possibility, we reviewed four additional meta-analyses that compared outcomes across two or more ethnic minority groups. Two compared outcomes across four groups (Griner & Smith 2006, and the others compared outcomes for black and Latino participants (Hodge et al 2010a;Huey & Polo 2008). Generally, no ethnic differences in treatment outcomes were found, although one meta-analysis (Smith et al 2011) showed that Asian Americans benefited more from psychotherapy than did African Americans, Latinos, and Native Americans (Figure 4).…”
Section: Do Psychotherapy Effects Differ By Ethnicity?mentioning
confidence: 99%
“…To assess this possibility, we reviewed four additional meta-analyses that compared outcomes across two or more ethnic minority groups. Two compared outcomes across four groups (Griner & Smith 2006, and the others compared outcomes for black and Latino participants (Hodge et al 2010a;Huey & Polo 2008). Generally, no ethnic differences in treatment outcomes were found, although one meta-analysis (Smith et al 2011) showed that Asian Americans benefited more from psychotherapy than did African Americans, Latinos, and Native Americans (Figure 4).…”
Section: Do Psychotherapy Effects Differ By Ethnicity?mentioning
confidence: 99%
“…Although the systematic adaptation and evaluation of whole school mental health promotion interventions do not have the same rich legacy of research, 'surface' and 'deep' considerations may operate here as well. Recent reviews of culturally sensitive interventions show some promising results in terms of effectiveness for Hispanic, African or First Nations American youth (Hodge, Jackson, & Vaughn, 2010;Huey & Polo, 2008;Jani, Ortiz, & Aranda, 2009). They indicate that cognitive, motivational and ecological qualities can enter a programme, such as local experiences and 'knowledges'.…”
Section: Advances In School Mental Health Promotionmentioning
confidence: 97%
“…While it is unclear whether a culturally appropriate program will be more effective in changing women's drinking behavior during pregnancy (Hawkins et al, 2004;Hodge et al, 2010), the process of engaging the community and gaining feedback on community priorities in the early phases of research was essential. Focus group participants also emphasized the value of cultural appropriateness, saying that interventions, including the language within them, must be understandable to the average community member and delivered only after consulting with tribal members.…”
Section: Discussionmentioning
confidence: 99%